Prevalence of bifid mandibular canal according to gender, type and side - Özlem Okumuş; Asım Dumlu (Elsevier, 2019)
Background/purpose: An awareness of mandibular canal variations may help prevent complications due to nerve damage that can occur during surgery. The aim of this study is to evaluate the variations of mandibular canal distribution and frequency via cone beam computed tomography (CBCT), retrospectively, in a Turkish population. Materials and methods: The study population comprises 500 (250 female, 250 male) randomly selected participants between the ages of 14 and 79 years. The study was conducted in Marmara University, Faculty of Dentistry, in the Department of Dentomaxillofacial Radiology. The distribution and frequency of mandibular canal variations were evaluated using the Naitoh classification, which includes retromolar canal, forward canal, dental canal, and buccolingual canal. The trifid canal was also included in this study. The data were analysed using IBM SPSS statistics 20.0. The data were then compared based on age group and gender. Results: Bifid mandibular canals (BMCs) were found in 200 (40%) of the 500 subjects, and in 248 of the 1000 sides (24.8%). Mandibular canal variations were observed in 71.5% of patients on the right side, 52.5% on left side and 24% bilaterally. The forward canal was the most common type (48.8%), followed by the retromolar canal (26.2%), the dental canal (12.9%), the buccolingual canal (9.7%), and the trifid canal (2.4%). Conclusion: BMCs were detected at a high rate in the Turkish subpopulation. Moreover, CBCT appears to be an appropriate method to assess the entity and shape of BMCs. Keywords: Anatomical variation, Bifid canal, Cone beam computed tomography, Mandibular canal, Trifid canal